If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + -3) = 6 Reorder the terms: 2x + 3(-3 + x) = 6 2x + (-3 * 3 + x * 3) = 6 2x + (-9 + 3x) = 6 Reorder the terms: -9 + 2x + 3x = 6 Combine like terms: 2x + 3x = 5x -9 + 5x = 6 Solving -9 + 5x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 5x = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 5x = 6 + 9 5x = 6 + 9 Combine like terms: 6 + 9 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 9(x-9)=8 | | -5(9)+2= | | 1-8z+24=-3z+1-7 | | 14-3*n=2 | | 0.2(0.1x+0.1)=-0.2 | | 7x+4.3-5.1x=0.3x-4.5 | | 2.25x+.14=.43x+.57 | | 2st^2+3s^2t-4st^2+14s^2t= | | 16-b^2=0 | | x^2-9x-3x-10=0 | | x^2-9x=3x-10 | | (4x^(2/3))-(19x^(1/3))-5=0 | | 2(8x+2)=50 | | .29x+.33=-.17x+.12 | | 22p+16=0.8986 | | -4.7x+1.9=-3.1x+2.3 | | 10+n*3=55 | | .29+.33=-.17+.12 | | (2x+4)+(3x-29)=180 | | 10+n*3=46 | | 2/3t^2-t=-1/6 | | -1/7x-8=-3 | | 4x^2/3-19x^1/3-5=0 | | -1/7x-8-3 | | 8z-10=6 | | 6(x-3)=5 | | 4.4y-4.9=4.9y-.04 | | 8-7y=2-y | | -14y+10=-14y-23 | | Y-2=7(x-3) | | 8z+3=6 | | 4v+2=2v-16 |